(untitled) (Archaeologia Adriatica, 2009)
In his paper the author analyzes a bow fibula found on the site of Jarebinjak in Brgud near Benkovac. Analyzes of its typological and stylistic characteristics, as well as comparison with fibulae from pannonian-danubian region, i.e. the territory of present-day Hungary, establish that fibula from Brgud should be attributed to the Gepids. It can be dated to the very end of the 5th century or the first three decades of the 6th century. In all probability, it was made in one of the local workshops in the territory of Dalmatia. Fibula from Brgud is a new contribution to the history of the Gepids in our territories in the time of Ostrogothic rule over Dalmatia. It is also additional indication for a supposition that the Roman settlement of Alveria should be placed on the Jarebinjak hill-fort.